2017
DOI: 10.3390/jintelligence5010004
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Less Is Not Enough: A Commentary on Greiff et al. (2015)

Abstract: In this commentary, I discuss some critical issues in the study by Greiff, S.; Stadler, M.; Sonnleitner, P.; Wolff, C.; Martin, R., “Sometimes less is more: Comparing the validity of complex problem solving measures”, Intelligence 2015 , 50 , 100–113. I conclude that—counter to the claims made in the original study—the specific study design was not suitable for deriving conclusions about the validity of different complex problem-solving (CPS) measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…For the latter, the quality of one’s hypotheses, which is based on domain knowledge, is a necessary prerequisite for successfully exploring the system. In summary, the features of MCS measurements outlined here, along with further criticisms of this approach (e.g., Funke, 2014; Scherer, 2015; Schoppek and Fischer, 2015; Dörner and Funke, 2017; Funke et al, 2017; Kretzschmar, 2017), substantially narrow the validity of the MCS approach as an indicator of CPS.…”
Section: Part Ii: Review and Critique Of The Minimally Complex Systemmentioning
confidence: 88%
See 4 more Smart Citations
“…For the latter, the quality of one’s hypotheses, which is based on domain knowledge, is a necessary prerequisite for successfully exploring the system. In summary, the features of MCS measurements outlined here, along with further criticisms of this approach (e.g., Funke, 2014; Scherer, 2015; Schoppek and Fischer, 2015; Dörner and Funke, 2017; Funke et al, 2017; Kretzschmar, 2017), substantially narrow the validity of the MCS approach as an indicator of CPS.…”
Section: Part Ii: Review and Critique Of The Minimally Complex Systemmentioning
confidence: 88%
“…On the other hand, the relevance of the MCS approach is shown by many studies that have modeled the internal structure of MCS tasks (e.g., Greiff et al, 2012; Sonnleitner et al, 2012), provided evidence that performance variance cannot be sufficiently explained by reasoning (e.g., Wüstenberg et al, 2012; Sonnleitner et al, 2013; Kretzschmar et al, 2016), found strong convergent validity as well as a lower correlation with a CRS (i.e., Tailorshop ; Greiff et al, 2015b; for a different view, see Kretzschmar, 2017), and demonstrated incremental validity in predicting school grades beyond reasoning (e.g., Greiff et al, 2013b; Sonnleitner et al, 2013; for different results, see Kretzschmar et al, 2016; Lotz et al, 2016) and beyond a CRS task (Greiff et al, 2015b). MCS have been proposed as a tool for assessing 21st Century skills (Greiff et al, 2014) and were applied in the international large-scale study PISA to assess general problem-solving skills (OECD, 2014).…”
Section: Part Ii: Review and Critique Of The Minimally Complex Systemmentioning
confidence: 99%
See 3 more Smart Citations